Wake up [videorecording (DVD)] - Craig, Janet; Horan, Dan; Gridley, David; Griffith, Tori; Singleton, Isaac C.; Houston, Chasnie (Hotline LLC, 2024)
A suburban community is shaken to the core when a pair of foster teenagers mysteriously disappear, uncovering a darkness hiding in plain sight. Tension builds, lives intersect and uncomfortable truths are exposed as the community races against time to save their youth in this crime suspense thriller inspired by true events.